2015
DOI: 10.1007/s12687-015-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

A study of consanguineous marriage as a risk factor for developing comitant strabismus

Abstract: Inheritance has an important role in the etiology of comitant strabismus. Consanguineous marriage is a leading factor in birth defects in which inheritance has a role. The aim of this study is to reveal if consanguineous marriage increases the risk of developing comitant strabismus. We included 461 patients who underwent primary surgery for comitant strabismus in Shiraz University Khalili Hospital (Fars province, southern Iran) between years 2003 and 2013 in our study. All the patients were living in Shiraz, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The high incidence of strabismus in our study is in line with the other studies related to vision screening among school children in Saudi Arabia [35,36]. These higher rates of strabismus among Saudi children may be due to higher prevalence of consanguinity due to more common marriage among relatives of the same families [37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…The high incidence of strabismus in our study is in line with the other studies related to vision screening among school children in Saudi Arabia [35,36]. These higher rates of strabismus among Saudi children may be due to higher prevalence of consanguinity due to more common marriage among relatives of the same families [37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…Ziakas et al (26.1%) and Bagheri et al (37.7%) had similar observations. 13,14 Prematurity, low birth weight, low Apgar scores, and a family history of strabismus are considered significant risk factors for strabismus. 15,16 Our study cohort had only 4% preterm born patients and 18% had history of neonatal ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies revealed a relation between consanguineous marriages and mental retardation, mortality in fetus and infants and strabismus [11][12][13]. The association between parental consanguinity and mental health is an important issue, research in this field has not been done in Iran.…”
Section: Introductionmentioning
confidence: 99%